2016
DOI: 10.1186/s12864-016-2946-1
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to identify housekeeping genes suitable for analysis in breast cancer diseases

Abstract: BackgroundThe selection of suitable internal control genes is crucial for proper interpretation of real-time PCR data. Here we outline a strategy to identify housekeeping genes that could serve as suitable internal control for comparative analyses of gene expression data in breast cancer cell lines and tissues obtained by high throughput sequencing and quantitative real-time PCR (qRT-PCR).MethodsThe strategy proposed includes the large-scale screening of potential candidate reference genes from RNA-seq data as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 27 publications
4
63
1
Order By: Relevance
“…Presumably these adaptations would take place in order to meet the energy demands needed for smoltification and for reorganizing tissues in preparation to life in seawater, which could be related to the higher abundance in smolts of serine-rich coiled-coil domain-containing protein 2, stathmin and fibronectin, all related to cell and microtubule organization [110][111][112]. Curiously, serine-rich coiled-coil domain-containing protein 2 has been proposed as a reliable housekeeping gene in humans but this is unlikely to be the case in rainbow trout given the present results [113].…”
Section: Discussionmentioning
confidence: 62%
“…Presumably these adaptations would take place in order to meet the energy demands needed for smoltification and for reorganizing tissues in preparation to life in seawater, which could be related to the higher abundance in smolts of serine-rich coiled-coil domain-containing protein 2, stathmin and fibronectin, all related to cell and microtubule organization [110][111][112]. Curiously, serine-rich coiled-coil domain-containing protein 2 has been proposed as a reliable housekeeping gene in humans but this is unlikely to be the case in rainbow trout given the present results [113].…”
Section: Discussionmentioning
confidence: 62%
“…CCSER2 is described as a "novel housekeeping gene" (nHKG) by Tilli et al [27], who provided evidence as to its use as a reference gene in breast cancer studies. They demonstrated that expression of CCSER2 is expected to be like the other nHKGs they identi ed that can increase the assessment consistency of normalization.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in the MIQE guidelines [24], normalization against a single reference gene is not recommended unless a clear evidence of its uniform expression dynamics is described for the speci c experimental conditions. Many studies have been undertaken previously identifying new stable reference genes over the previous two decades for MCF-7 cell line or breast cancer as whole [25,26,27,28,29,30,31,32].…”
Section: A Widely Accepted Technique For Validation Of Gene Expressiomentioning
confidence: 99%
See 1 more Smart Citation
“…The internal control gene chosen, therefore, has to be stably expressed and show no difference in expression levels between groups, independent of the tissue type, cell line, experimental conditions, development stage, or disease state [11][12][13] . However, it has been recently shown by many different groups that under certain non-physiological or experimental conditions, the levels of the most commonly used internal control or housekeeping genes in fact change, and are particularly affected in cancer 12,[14][15][16][17][18][19][20] . For example, studies validating housekeeping genes in glioblastoma show that TBP has been the most stable internal control whereas GAPDH shows significant differences between tumour samples and controls 15,19 .…”
Section: Introductionmentioning
confidence: 99%